Analysis of international legal protection of the existence of the state of Palestine and the legality of Israel's counter-attacks against the attacks launched by Hamas - Roniya Yudha Sanjaya (Goodwood Publishing, 2023)
Purpose: This study is expected to provide significant scientific contributions in understanding the dynamics of international law in the context of armed conflict, as well as providing policy recommendations to strengthen efforts for a peaceful resolution. Research/methodology: This study uses a normative legal method with a case approach and is analyzed based on relevant international legal principles, including the Charter of the United Nations, the Geneva Conventions, and international humanitarian law. Conclusions: This study concludes that although the right to self-defense is recognized internationally, its implementation must always be in line with the principles of justice, humanity, and applicable law to avoid things that can worsen the humanitarian situation. Contributions: this study provides a significant scientific contribution in understanding the dynamics of international law in the context of armed conflict, as well as providing policy recommendations to strengthen efforts for peaceful resolution.